The effect of using the bee model to solve the engineering problem The first graders have an average and their mental motivation - Haider Abdulzahra Alwan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
This study aimed at identifying the effect of using a model of Allen Hoover for the female students of first class on their, geometric problem solving and mental motivation. To achieve the goal of this study, developed two null hypotheses below: 1) There not were significant difference at (α ≤ 0.05) in the test geometric problem solving between the mean of marks of the female students in research groups (experimental and control). 2) There not were significant difference at (α ≤ 0.05) in the scale mental motivation between the mean of marks of the female students in research groups (experimental and control).